Detection of known haemophilia B mutations and carrier testing by microarray - Chan, Kaimin; Sasanakul, W.; Mellars, Gillian; Chuansumrit, Ampaiwan; Perry, D; Lee, Christine A; Wong, Man-Sim; Chan, Tai-Kwong; Chan, Vivian (Thrombosis and Haemostasis, 2005)
The molecular basis of haemophilia B is heterogeneous and many mutations of the Factor IX (FIX) gene have been characterised. Using the allele-specific arrayed primer extension (ASAPEX) technology, we have designed a FIX array to simultaneously analyse 69 mutations found in British, Thai and Chinese patients. This technology overcomes the problem of multiple reverse dot-blot analysis and has a 100% accuracy in the detection of both affected subjects and carriers in families with known mutations. In seven unknown mutations from Thailand, the array could detect the specific mutation in five and in the remainders the normal primer at specific spots failed to extend due to a mutation a few nucleotides upstream, thus allowing their identification. Hence this FIX array can detect 53% of the 2891 mutation entries in the FIX database. Each of the microarray slide can be used for three different test samples and would be useful for carrier testing for common mutations and prenatal diagnosis. It is simpler and more cost effective than genome sequencing and would be particularly useful in laboratories with limited technical capabilities.
Keywords: Haemophilia B; FIX microarray; AS-APEX; FIX mutations